Influence of Parent Involvement to Childrens Learning Intrest During Corona Virus Pandemic - Manan Manan; La Jeti; Adnan Adnan (LPPM Universitas Pahlawan Tuanku Tambusai, 2021)
This research aimed to obtain information about influence of parental involvement on children's learning interests at home during the corona virus pandemic. This research used a quantitative approach to the type of ex-post facto research. The population in this research consisted of 90 parents and students. This research was conducted in Buton Regency. The data collection method used a questionnaire and used simple regression analysis. Based on the hypothesis tested, it found a positive and significant influence on children's interest in learning at home during the corona virus pandemic with a regression coefficient of 72,749 and a significant value (sig) of 0,000 0.05. Parents' involvement in the parenting in program was to provide support, respect the work of children, guide, supervise and discipline. Teaching children at home, Providing motivation, Building good communication with children and school environment to find out the child's development, Building cooperation with schools and the community.